A light-activated magnetic bead strategy utilized in spatio-temporal controllable exosomes isolation - Wang, Chenhan; Zhang, Duoteng; Yang, Haiyan; Shi, Liang; Li, Lin; Yu, Changmin; Wei, Jifu; Ding, Qiang (Frontiers in Bioengineering and Biotechnology, 2022)
Tumor-derived exosomes are considered as a key biomarker in the field of liquid biopsy. However, conventional separation techniques such as ultracentrifugation, co-precipitation and column chromatography cannot isolate samples with high throughput, while traditional immunomagnetic separation techniques, due to the steric effect of magnetic beads, reduce the sensitivity of optical detection of exosomes. Herein, we provide a novel and simple nanoplatform for spatiotemporally controlling extraction and elution of exosomes via magnetic separation and light-activated cargo release. In this system, magnetic beads are co-modified by photoresponsive groups -nitrobenzyl group and aptamers that are compatible with CD63-a highly expressed exosomal surface-specific protein. Through exosomes extracted from cell model and nude mice xenograft tumor model morphological characterization and proteomic analysis, it showed that our novel magnetic bead system outperformed current ultracentrifugation in serum exosome extraction in terms of extraction time, yield, and proportion of populations with high CD63 expression. This strategy may be a powerful tool for exosome isolation in clinical liquid biopsies of cancer disease.